PERANCANGAN APLIKASI POINT OF SALE BERBASIS WEB PADA BELIG COFFE MENGGUNAKAN EXTREME PROGRAMMING - Tomy Rizmawan; Daffa Satria Maulana; Bara Pentium Alarsy; Roeslan Djulatov (Shofanah Media Berkah, 2023)
In this era, technology is increasingly sophisticated and modern. Everyone is required to be fast and accurate in working, in the world of working machines or technology are growing, as well as the cashier transaction system at the BATU BELIG COFFE Shop, currently the shop does not have a computerized system. So that in making receipt numbers or receipts using a manual system, namely by handwriting, this can cause the number to be the same or double. Also on the creation of a report each incoming receipt is stacked on a folder. This can also cause the receipt to be lost, tucked away or damaged. In the study, the title